Wastewater effluents cause microbial community shifts and change trophic status. (15th July 2021) - Ruprecht, J.E.; Birrer, S.C.; Dafforn, K.A.; Mitrovic, S.M.; Crane, S.L.; Johnston, E.L.; Wemheuer, F.; Navarro, A.; Harrison, A.J.; Turner, I.L.; Glamore, W.C.
Highlights: Microbes are sensitive to environmental stressors, such as wastewater pollution. This study combined novel methods of microbial ecotoxicology in the field and lab. Wastewater effluents caused community shifts above moderate (>10%) concentrations. Riverine community shifts were explained by two potentially globally relevant keystone taxa. Malikia spp. and hgcI_clade proposed as indicators of changes in trophic status. Abstract: Widespread wastewater pollution is one of the greatest challenges threatening the sustainable management of rivers globally. Understanding microbial responses to gradients in environmental stressors, such as wastewater pollution, is crucial to identify thresholds of community change and to develop management strategies that protect ecosystem integrity. This study used multiple lines of empirical evidence, including a novel combination of microbial ecotoxicology methods in the laboratory and field to link pressure-stressor-response relationships. Specifically, community-based whole effluent toxicity (WET) testing and environmental genomics were integrated to determine real-world community interactions, shifts and functional change in response to wastewater pollution. Here we show that wastewater effluents above moderate (>10%) concentrations caused consistent significant shifts in bacterial community structure and function. These thresholds of community shifts were also linked to changes in the trophic state of receiving waters in terms of nutrient concentrations. Differences in the community responses along the effluent concentration gradient were primarily driven by two globally relevant bacterial indicator taxa, namely Malikia spp. (Burkholderiales) and hgcI_clade (Frankiales). Species replacement occurred above moderate effluent concentrations with abundances of Malikia spp. increasing, while abundances of hgcI_clade decreased. The responses of Malikia spp. and hgcI_clade matched gene patterns associated with globally important nitrogen cycling pathways, such as denitrification and nitrogen fixation, which linked the core individual taxa to putative function and ecosystem processes, rarely achieved in previous studies. This study has identified potential indicators of change in trophic status and the functional consequences of wastewater pollution. These findings have immediate implications for both the management of environmental stressors and protection of aquatic ecosystems. Graphical abstract: Image, graphical abstract